The fashion system and the ephemeral: ballet and costume - O’Brien, Caroline (Textile and Design Lab and Colab at Auckland University of Technology, 2014)
This paper interrogates the theory that dress is synonymous with the identity of the ballerina. Rooted in the seventeenth century French court, classical ballet is perhaps our last vestige of aristocratic manners and civility. The early court dances were encumbered by dress of the day, arguably identifiable in its silhouette and material composition. In 1832 Marie Taglioni made a landmark contribution to the ballet, the combination of the romantic tutu and the satin slippers that allowed her to elevate onto her toes. The ballerina evolved over the nineteenth and twentieth centuries as an iconic symbol of feminine virtue, permitting an earthbound mortal with a gift for movement to transcend her corporeal bonds and hover over the earth. The religion of the ballerina might be described as an art of high ideals and self-control in which a public aristocratic bearing and grace symbolize private virtue and an elevated state of being. The classical tutu is an esoteric garment, an evolution of theatrical pragmatism and ephemeral fashion, but in its lightness, sparkle and elegance, in the craft and dedication that go into its making, the tutu embodies everything that ballet is about. This paper considers the ways the tutu constructs and articulates an appropriate ballerina femininity, demonstrating that this iconic functional artefact of the ballet is beautiful in its own right. Expressive of the dichotomy inherent to the life of the ballerina, the pristine surface exists in sharp contrast to the stains of sweat and makeup combined with the tang of anxiety embedded in the layers, illuminating the signs of a ballerina’s work. The trained and honed contours of the ballerina body become transformed in the adoption of the carapace that is the bodice bordered with a wide froth of pleated netting. The garment offers a fragile, protective space that defines a boundary between the unfinished, vulnerable, leaky-at-the-margins body and the pristine and glittering seamless surface. The geometric and architectural shapes performed by the ballerina present an infinitely recognizable silhouette on the stage. The ballet costume sustains and is sustained by the aristocratic codes of manners and behaviour, and has continued to transform itself innumerable times during its history. If classical ballet is about movement, theatrical presentation and storytelling, the tutu becomes the only material evidence of the performance while the dance itself remains an ephemeral art form, leaving no record.